Hydrated Lime–Based Coating for Cool Pavement Technologies: Evaluation of Durability and Thermal Performance - Muhammad Khuzamy; Taqia Rahman; Imtiaz Ahmed; Syed Bilal Ahmed Zaidi (Journal of the Civil Engineering Forum, 2026)
Heat-reflective pavement coatings are commonly employed for road cooling and to mitigate Urban Heat Island (UHI) effects by reflecting solar radiation and reducing surface temperatures. However, their cooling efficiency diminishes over time due to abrasion, soiling, UV exposure, and environmental aging, which degrade the reflective polymer layer. As a cost-effective alternative, hot-rolled hydrated lime (HL) applied to pavement surfaces has emerged, forming a light-coloured mineral layer that enhances reflectivity and potentially reduces pavement temperature. This study investigates hydrated lime (HL) as a mineral-based alternative, applied through hot-rolling to form a reflective surface layer that is compatible with conventional asphalt practices. Its performance was evaluated through laboratory thermal simulations (day–night cycling) and abrasion wear testing and compared with three commercial paint-based HRCs: epoxy resin–TiO₂ and acrylic emulsion–TiO₂. The results show that HL coatings achieved surface temperature reductions of up to 21.89 °C compared to uncoated asphalt, exceeding the best-performing paint-based sample (White-AE, 19.29 °C), suggesting that HL has strong potential as an effective reflective coating. This was achieved with a formulation of fine HL particles (No. 400 mesh) at a higher dosage (200 g/m²). In abrasion resistance tests, HL outperformed paint based HRCs, with lower mass losses (0.6–1.3 g vs. 0.8–1.5 g), which was attributed to stronger adhesion and particle embedment. In addition, post-abrasion tests revealed that HL samples retained better thermal stability, with smaller temperature increases (ΔT: 5.9–6.8 °C) than HRCs (ΔT: 6.3–7.2 °C). Based on these outcomes, HL applied at 200 g/m² using fine particles (No.400 mesh) is recommended as the optimal formulation for maximizing cooling performance and surface durability. Overall, these findings suggest that hot-rolled HL is a durable, low-cost, and effective alternative cooling strategy to popular HRCs for UHI mitigation.